PERANCANGAN PEDETEKSI JUMLAH TETESAN PADA ALAT INFUST PUMP MERK TERUMO - M Yasir Pohan (LPPM Universitas Cipta Mandiri, 2026)
Infusion pump is a tool that is most often used in the medical world, which serves to provide fluids to patients. The purpose of using an infusion pump is to maintain the administration of excessive or inappropriate fluids. If there is an error in giving the dose of intravenous fluids, it can be bad for the patient. Therefore, it is necessary to detect the number of drops on the infusion pump or what is often called a Drip sensor, which functions to detect how many drops have been given by the infusion. The results of the settings on the infusion pump unit that have been determined, must be in accordance (balanced) with how many drops have been counted by the drip sensor detection circuit (Drip sensor). In the drip detection circuit, the Terumo TE112 brand infusion pump has important component, namely infrared and photo diode. In the drip sensor circuit, the Infra red is the transmitter (sender), and the photo diode is the receiver, which is also known as the sensor